A novel crosstalk between autophagosomes and phagosomes that facilitates the clearance of apoptotic cells. Issue 6 (3rd June 2022) - Zhou, Zheng; Peña-Ramos, Omar
ABSTRACT: During an animal's life, many cells undergo apoptosis, a form of genetically programmed cell death. These cells are swiftly engulfed by other cells through phagocytosis and subsequently degraded inside phagosomes. Phagocytosis and macroautophagy/autophagy are two different cellular events: whereas phagocytosis is a cell-eat-cell event, autophagy, or "self-eating", occurs within one cell, resulting in the enveloping of protein aggregates or damaged organelles within double-membrane autophagosomes. Despite this critical difference, these two events share common features: (1) both are means of safe garbage disposal; (2) both phagosomes and autophagosomes fuse to lysosomes, which drive the degradation of their contents; and (3) both events facilitate the recycling of biological materials. Previously, whether autophagosomes per se directly participate in the degradation of apoptotic cells was unknown, although autophagy proteins were implicated in apoptotic cell clearance. We recently discovered that autophagosomes fuse with phagosomes and contribute to the degradation of apoptotic cells.